Does human endometrial LGR5 gene expression suggest the existence of another hormonally regulated epithelial stem cell niche?. Issue 6 (10th April 2018) - Tempest, N; Baker, A M; Wright, N A; Hapangama, D K
Abstract: STUDY QUESTION: Is human endometrial leucine-rich repeat-containing G-protein-coupled receptor 5 (LGR5) gene expression limited to the postulated epithelial stem cell niche, stratum basalis glands, and is it hormonally regulated? SUMMARY ANSWER: LGR5 expressing cells are not limited to the postulated stem cell niche but LGR5 expression is hormonally regulated. WHAT IS KNOWN ALREADY: The human endometrium is a highly regenerative tissue; however, endometrial epithelial stem cell markers are yet to be confirmed. LGR5 is a marker of stem cells in various epithelia. STUDY DESIGN, SIZE, DURATION: The study was conducted at a University Research Institute. Endometrial samples from 50 healthy women undergoing benign gynaecological surgery with no endometrial pathology at the Liverpool Women's hospital were included and analysed in the following six sub-categories; proliferative, secretory phases of menstrual cycle, postmenopausal, those using oral and local progestagens and samples for in vitro explant culture. PARTICIPANTS/MATERIALS, SETTING, METHODS: In this study, we used the gold standard method, in situ hybridisation (ISH) along with qPCR and a systems biology approach to study the location of LGR5 gene expression in full thickness human endometrium and Fallopian tubes. The progesterone regulation of endometrial LGR5 was examined in vivo and in short-term cultured endometrial tissue explants in vitro . LGR5 expression was correlated with epithelial proliferation (Ki67), and expression of previously reported epithelia progenitor markers (SOX9 and SSEA-1) immunohistochemistry (IHC). MAIN RESULTS AND THE ROLE OF CHANCE: LGR5 gene expression was significantly higher in the endometrial luminal epithelium than in all other epithelial compartments in the healthy human endometrium, including the endometrial stratum basalis ( P < 0.05). The strongest SSEA-1 and SOX9 staining was observed in the stratum basalis glands, but the general trend of SOX9 and SSEA-1 expression followed the same cyclical pattern of expression as LGR5. Stratum functionalis epithelial Ki67-LI and LGR5 expression levels correlated significantly ( r = 0.74, P = 0.01), however, they did not correlate in luminal and stratum basalis epithelium ( r = 0.5 and 0.13, respectively). Endometrial LGR5 demonstrates a dynamic spatiotemporal expression pattern, suggesting hormonal regulation. Oral and local progestogens significantly reduced endometrial LGR5 mRNA levels compared with women not on hormonal treatment ( P < 0.01). Our data were in agreement with in silico analysis of published endometrial microarrays. LARGE SCALE DATA: We did not generate our own large scale data but interrogated publically available large scale data sets. LIMITATIONS, REASONS FOR CAUTION: In the absence of reliable antibodies for human LGR5 protein and validated lineage markers for the various epithelial populations that potentially exist within the endometrium, our study does not formally characterise or examine the functional ability of the resident LGR5 + cells as multipotent. WIDER IMPLICATIONS OF THE FINDINGS: These data will facilitate future lineage tracing studies in the human endometrial epithelium; to identify the location of stem cells and further complement the in vitro functional studies, to confirm if the LGR5 expressing epithelial cells indeed represent the epithelial stem cell population. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by funding from the Wellbeing of Women project grant (RTF510) and Cancer Research UK (A14895). None of the authors have any conflicts of interest to disclose.